1985
DOI: 10.1002/1097-0142(19850215)55:4<738::aid-cncr2820550410>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid differentiation in ovarian sex cord tumor with annular tubules accompanied by gestagenic effect

Abstract: A case of ovarian sex cord tumor with annular tubules (SCTAT) without Peutz‐Jeghers syndrome is presented in which portions of the neoplasm showed endometrioid differentiation. In addition, histologic examination of endometrium obtained from curettings and hysterectomy specimen revealed atrophic glands and a decidual type stroma, indicating a possible gestagenic effect of the ovarian tumor. The latter has so far been only briefly alluded to in the literature, whereas to the best of the authors' knowledge, endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other features noted in the right-sided tumor, such as foci of more elongated tubules and a diffuse pattern of arrangement of tumor cells, are also well documented. However, previous reports of both benign and malignant SCTAT, including both sporadic and PJS-associated tumors, have described additional histologic patterns such as sertoliform tubules, endometrioid areas, and foci of granulosa cell-like differentiation (1,6,7,(12)(13)(14). On the basis of such findings, some authors have suggested that SCTAT represent variants of either Sertoli cell or granulosa cell tumors, whereas others regard SC-TAT as distinctive neoplasms with features intermediate between those of Sertoli cell and granulosa cell tumors (1, 2, 6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Other features noted in the right-sided tumor, such as foci of more elongated tubules and a diffuse pattern of arrangement of tumor cells, are also well documented. However, previous reports of both benign and malignant SCTAT, including both sporadic and PJS-associated tumors, have described additional histologic patterns such as sertoliform tubules, endometrioid areas, and foci of granulosa cell-like differentiation (1,6,7,(12)(13)(14). On the basis of such findings, some authors have suggested that SCTAT represent variants of either Sertoli cell or granulosa cell tumors, whereas others regard SC-TAT as distinctive neoplasms with features intermediate between those of Sertoli cell and granulosa cell tumors (1, 2, 6, 7).…”
Section: Discussionmentioning
confidence: 99%